Postmenopausal serous giant ovarian cystadenoma. A case report - Ayala Peralta, Félix Dasio (2020)
Serous ovarian cystadenoma is a type of tumor derived from the superficial celomic epithelium. Giant ovarian cysts are those that are more than 10 cm in diameter or that extend above the navel. In the literature, some cases of giant ovarian cysts have been mentioned sporadically, especially in postmenopausal patients. Serous tumors are commonly benign in 70-80%, 5-10% have a malignant potential limit, and 20-25% are malignant. Only 10-20% of cases are bilateral.  They occur in adults of all ages, with reported mean ages of 40 to 60 years. The case of a 79-year-old postmenopausal woman with a giant left ovarian cyst measuring 14x11x7.5 cm and 794 g of weight containing serous fluid is reported. He came to the clinic for presenting colic-type pelvic pain irradiated to the lumbar region for 4 months with a history of chronic arterial hypertension.. Considering the age and status of menopause, laparotomy for a left cystectomy is performed without any significant complications. On histopathological examination, the cyst was confirmed as benign serous cystadenoma of the ovary. It had a favorable postoperative evolution.